Estimasi Tinggi Badan berdasarkan Panjang Tulang Femur pada Mahasiswa Suku Bugis Universitas Muslim Indonesia - Zulfiyah Surdam; Armanto Makmun; Mona Nulanda; Rezky Putri Indarwati; Handi Ardiansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Identification is an important examination in determining a person's identity in forensic anthropology. One of the parameters that can be used to determine a person's biological profile is height. Estimation of height based on the length of the femur is the most widely used method, because it has a significant correlation coefficient value to height. The purpose of this study was to determine the estimation of height based on the length of the femur in the Bugis. This research is a descriptive analytic study with a cross sectional approach to 40 students of the Faculty of Medicine UMI who are Bugis ethnicity with purposive sampling technique. Data analysis was performed by using Pearson correlation test and simple linear regression test. The results obtained that the mean height of the male is 171.42 ± 5.63, the female is 153.91 ± 6.18, the mean length of the right femur for the male is 44.54 ± 3.20 and the left is 44.32 ± 3.19, while the length of the left femur for women is 37.15 ± 3.12, and the right is 37.18 ± 3.05. With Pearson correlation analysis, obtained r value between 0.828 and 0.928 which indicates a significant correlation. The regression formula obtained between the length of the left femur and height in men is Height = 100,627 + 1,597 x (Left Femur for Men), while for the right femur, Height = 98,772 + 1,631 x (Right Femur for Men). The regression formula for the length of the female left femur and height is Height = 92.891+1.643 x (Female Left Femur) while the length of the female right femur is Height = 88.528+1.758 (Female Right Femur). This formula can be used on the Bugis. Height can be estimated by measuring the length of the femur using a linear regression equation.